Prevalence, predictive factors, and survival outcome of new-onset diabetes after liver transplantation: A population-based cohort study. Issue 25 (June 2016) - Liu, Fu-Chao; Lin, Jr-Rung; Chen, Hsiu-Pin; Tsai, Yung-Fong; Yu, Huang-Ping
Abstract : Abstract: The aim of the present nationwide population-based cohort study was to explore the prevalence, risk factors, and survival outcome of new-onset diabetes (NOD) in recipients after liver transplantation. The National Health Insurance Research Database of Taiwan was searched for ICD-9-codes, 2248 patients who had received liver transplant without pretransplant diabetes from July 1, 1998 to December 31, 2012 were included in the study. The preoperative risks factors were considered and analyzed using logistic regression analysis, following adjustments for age and sex. All patients were followed up until the end of the study or death. The final dataset included 189 patients with NOD and 2059 without diabetes after liver transplantation. The prevalence of NOD was 8.4% and in 64% NOD appeared in the first year after liver transplantation. Preoperative clinical events, alcoholic liver cirrhosis, and hepatic encephalopathy were the most important risk factors for NOD after liver transplantation. The mortality rate was lower in NOD recipients than in non-NOD recipients within 5 years. In this study, we provide evidence that NOD recipients had better 5-year survival outcomes in this clinical population. The most important identifiable predictive factors for NOD after liver transplantation were alcoholic hepatitis, ascites, hepatic coma, and esophageal varices. Abstract : Supplemental Digital Content is available in the text